Turning Points in Adolescent Analysis: An Introduction to the Section. Issue 1 (1st January 2020) - Chused, Judith Fingert
ABSTRACT: In the introduction to a panel on Turning Points in Adolescent Analysis, the author raises the questions of what constitutes a turning point and what factors in the work contribute to it. She also challenged the panelists to examine how their theoretical and clinical understanding of optimal psychoanalytic technique, when they differed with each other's, colored their understanding of what was mutative in the process and what led to turning points.